Momentary stress, cortisol, and gestational length among pregnant victims of childhood maltreatment: a pilot study. (June 2016) - Bublitz, Margaret H; Bourjeily, Ghada; Vergara-Lopez, Chrystal; Stroud, Laura R
Background: Pregnant victims of childhood maltreatment are more likely to deliver preterm. The mechanisms explaining this relationship are unclear. The goal of the current pilot study was to investigate whether momentary stress and cortisol serve as mechanisms linking maltreatment history to gestational length. Methods: Seventeen women enrolled in the study (35% maltreated). Women completed two study sessions at 27 and 34 weeks gestation. Following each session, at four times/day over two days, women reported their momentary stress levels by text message and provided corresponding salivary cortisol samples. Gestational length was determined by medical chart review. Results: Higher reports of momentary stress were associated with shortened gestational length. High stress predicted lower cortisol concentrations for women with maltreatment histories but higher concentrations among women without maltreatment. Conclusion: Results from this pilot study provide preliminary evidence for understanding mechanisms explaining increased risk for preterm birth among childhood maltreatment victims.